Postrzeganie wegańskiej oferty rynkowej przez konsumentów w Polsce w świetle badań ankietowych - Mocarska, Alicja (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
Industrial livestock farming is recognized as the main cause of the deteriorating state of the natural environment (especially greenhouse gas emissions), animal suffering and health problems such as obesity and colorectal cancer. In view of the above, the number of people in the world, which completely excludes the consumption of animal products is increasing. This growing trend on a global scale, which is veganism, is also present among Poles. Food manufacturers – both new and those with many years of market experience – did not remain passive about the popularity of plant-based products. Therefore, on store shelves, you can see a widespread vegan assortment introduced for distribution not only in specialist stores, but also in popular discount stores. The main purpose of this article is to present the one’s own research report, thanks to which the perception of vegan market offer by consumers in Poland was analyzed. In the primary data collection, online questionnaires posted on the Facebook social platform in vegan groups were used, which resulted in the deliberate sampling selection. The research was carried out in March 2021. The number of respondents amounted to 1,581 people. The main buyers of vegan products in Poland turned out to be people from two age groups: 18–24 and 25–30, coming from large cities, with higher education and with a significant majority of women over men. Findings suggest that the main motive for the consumption of vegan food products among Poles is concern for animal welfare. The vast majority agreed that products such as vegan substitutes for cheese, sweets, ice cream and yoghurts are lacking the most in stores. The analysis of the conducted research allowed for the formulation of the following conclusions: the surveyed group overall agrees that the offer of plant – based products in Poland is at a good level. The obtained results also confirmed the thesis that young people are more aware of the negative effects coming from consumption of animal products.
Keywords: veganism; plant – based products; consumer behaviour